2020
DOI: 10.1016/j.ijhm.2020.102664
|View full text |Cite
|
Sign up to set email alerts
|

Reducing perceived health risk to attract hotel customers in the COVID-19 pandemic era: Focused on technology innovation for social distancing and cleanliness

Abstract: Highlights Hotels can reduce customers’ perceived health risk via technology innovation. Technology innovation can achieve social distancing and enhance cleanliness in the COVID-19 era. Perceived health risk mediates the relationship between expected interaction and booking intention. Perceived cleanliness moderates the impact of expected interaction on perceived health risk. The perceived health risk mechanism is effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
373
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(472 citation statements)
references
References 54 publications
17
373
0
16
Order By: Relevance
“…Previous studies have suggested the salient role of safety and security when customers select a hotel. Safety and security are regarded as factors that people find important more than ever since the onset of COVID-19 [6]. This study validated that consumers perceive a greater degree of safety and security at smart hotels, as well as the influence of safety and security on the development of individual attitudes toward a smart hotel.…”
Section: Managerial Implicationssupporting
confidence: 63%
See 2 more Smart Citations
“…Previous studies have suggested the salient role of safety and security when customers select a hotel. Safety and security are regarded as factors that people find important more than ever since the onset of COVID-19 [6]. This study validated that consumers perceive a greater degree of safety and security at smart hotels, as well as the influence of safety and security on the development of individual attitudes toward a smart hotel.…”
Section: Managerial Implicationssupporting
confidence: 63%
“…More recently, Go [36] discussed robots with machine learning applications, which are built to protect the customers' safety and security in the hospitality industry. In addition, the COVID-19 pandemic generates many cases where technologies play a better role in crisis management, because they offer smart solutions with support in order to avoid human-to-human interactions [6,11,37].…”
Section: Expected Benefits Towards a Smart Hotelmentioning
confidence: 99%
See 1 more Smart Citation
“… Farmaki et al (2020) utilized interviews with P2P accommodation hosts to examine the impacts of COVID-19 on peer-to-peer accommodation platforms. Shin and Kang (2020) conducted three experimental studies using online survey samples to examine the impact of expected interaction and expected cleanliness on perceived health risk and hotel booking intention. Furthermore, purchasing online food deliveries ( Cai and Leung, 2020 ) and factors determining customers’ experience using food delivery apps during the COVID-19 pandemic period ( Zhao and Bacao, 2020 ) has also been analyzed.…”
Section: Literature Revie Wmentioning
confidence: 99%
“…While many studies have researched the revisit intention of hotel guests and its importance continues to be emphasized ( Han & Hyun, 2017 ; Jones et al, 2000 ; Kim et al, 2017 ; Scarpi et al, 2019 ), no studies have examined the perceived risk of hotel guests in the face of a new epidemic such as COVID-19 and its influence on the PTSD development and behavioral intentions of guests. Most studies have also focused on the negative impacts of COVID-19 and past pandemics (e.g., SARS and MERS) on the hospitality and tourism industry from the viewpoint of consumers' risk perception and restrictive purchase behaviors ( Joo et al, 2019 ; Pine & McKercher, 2004 ; Shin & Kang, 2020 ; Yu et al, 2021 ). Such studies intensively discuss the negative impacts of COVID-19 on the overall hospitality industry.…”
Section: Introductionmentioning
confidence: 99%